Deskripsi Minat Belajar Matematika Siswa Melalui Penerapan Model Pembelajaran Discovery Learning - Wahyuni, Nana; Rusdi, Rusdi; Leni, Nofri (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
Interest is a component that arouses someone's enthusiasm that causes that person to focus on a particular activity. The purpose of this research was to describe or describe students' interest in learning mathematics through the application of the Discovery Learning learning model while studying. This type of research is a quantitative descriptive research. The research subjects chosen were 26 students of SMP Negeri 1 Padang Panjang. The sampling technique used in this study was sampling involving all research subjects. Such a sampling technique is known as saturated sampling technique.  Researchers chose research instruments in the form of observation and questionnaires or questionnaires of interest in learning mathematics. Information was obtained that 75% of students felt happy participating in learning mathematics, 71% of students were involved in  learning mathematics, as many as 80% of students paid attention to learning mathematics, and 76% of students were also interested in learning mathematics. In the future, it is hoped that teachers will pay more attention to whether students are interested or not during mathematics learning, because students usually view mathematics as a subject that is considered difficult and is not of interest to students. Minat adalah suatu komponen yang membangkitkan semangat seseorang yang menyebabkan orang tersebut menjadi fokus terhadap suatu aktivitas tertentu. Tujuan penelitian ini dilakukan adalah untuk mendeskripsikan atau menggambarkan minat belajar matematika siswa terhadap pembelajaran matematika melalui diterapkannya model pembelajaran Discovery Learning saat belajar. Jenis penelitian yang dilakukan ini adalah penelitian deskriptif kuantitatif. Subjek penelitian yang dipilih adalah 26 orang siswa dan siswi SMP Negeri 1 Padang Panjang . Teknik sampling yang digunakan dalam penelitian ini adalah pengambilan sampel dengan melibatkan semua subjek penelitian. Teknik sampling yan demikian dikenal dengan teknik sampling jenuh.  Peneliti memilih instrumen penelitian berupa observasi dan kuesioner atau angket minat belajar matematika. Diperoleh informasi bahwa 75 % siswa merasa senang dalam mengikuti pembelajaran matematika, 71 % siswa ikut terlibat selama pembelajaran matematika, sebanyak 80 % siswa memberikan perhatiannya terhadap pembelajaran matematika, dan 76% siswa juga tertarik dengan pembelajaran matematika. Untuk kedepannya diharapkan guru lebih memperhatikan apakah siswa berminat atau tidak selama pembelajaran matematika, karena biasanya siswa memandang matematika sebagai mata pelajaran yang dianggap sulit dan tidak diminati oleh siswa.